English as a second language and outcomes of patients presenting with acute coronary syndromes: results from the CONCORDANCE registry. Issue 6 (4th April 2016) - Juergens, Craig P; Dabin, Bilyana; French, John K; Kritharides, Leonard; Hyun, Karice; Kilian, Jens; Chew, Derek PB; Brieger, David
Abstract: Objectives: To investigate whether patients with English as their second language have similar acute coronary syndrome (ACS) outcomes to people whose first language is English. Design: Retrospective, observational study, using admissions, treatment and follow‐up data. Participants and setting: : A total of 6304 subjects from 41 sites enrolled in the investigator‐initiated CONCORDANCE ACS registry. Main outcome measures: Baseline characteristics, treatments, and in‐hospital and 6‐month mortality. Results: English as a second language (ESL) was reported by 1005 subjects (15.9%). Patients with English as their first language (EFL) were older, and were less likely to have diabetes mellitus or to smoke than the ESL patients. Prior myocardial infarction, heart failure and chronic renal failure were more common in the ESL group. In‐hospital mortality was also higher in these patients (7.1% v 3.8% for EFL patients; P < 0.001). Predictors of in‐hospital mortality included presentation in cardiogenic shock, cardiac arrest in hospital, a history of renal failure, prior cardiac failure, and ESL. Rates of cardiac catheterisation, percutaneous coronary intervention rates, and referral to cardiac rehabilitation were lower in the ESL group; at 6 months, all‐cause mortality was also higher (13.8% v 8.3% for EFL group; P < 0.001). Logistic regression identified language, age, in‐hospital renal failure, and recurrent ischaemia as predictors of 6‐month mortality. Conclusion: Patients presenting with an ACS who report English as their second language have poorer outcomes than patients who use English as their first language. This difference may not be entirely explained by baseline demographic disparities or management differences.